OECD scan of equality budgeting in Ireland: Equality mainstreaming and inclusive policy making in action - Nicol, Scherie (OECD Publishing, 2021)
This article takes stock of actions that the government of Ireland has taken to mainstream equality considerations into the budget process. It provides options and recommendations on future directions for equality budgeting in Ireland, in light of national developments and international experience. These take into account the standards set out in the 2015 OECD Recommendation of the Council on Gender Equality in Public Life and the 2015 OECD Recommendation of the Council on Budgetary Governance. The scan also provides guidance to strengthen Ireland's institutional approach to equality proofing more holistically